2002
DOI: 10.1103/physrevd.65.084030
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational field around a screwed superconducting cosmic string in scalar-tensor theories

Abstract: We obtain the solution that corresponds to a screwed superconducting cosmic string (SSCS) in the framework of a general scalar-tensor theory including torsion. We investigate the metric of the SSCS in Brans-Dicke theory with torsion and analyze the case without torsion. We show that in the case with torsion the space-time background presents other properties different from that in which torsion is absent. When the spin vanish, this torsion is a φ-gradient and then it propagates outside of the string. We invest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Torsion can be related to coupling to fermionic fields [5], alternatively it can be associated with a scalar field gradient for bosons in scalar tensor theories [6,7] or to a rank 2 antisymmetric Kalb-Ramond tensor field as in [3,8].…”
Section: Jhep03(2005)039mentioning
confidence: 99%
See 1 more Smart Citation
“…Torsion can be related to coupling to fermionic fields [5], alternatively it can be associated with a scalar field gradient for bosons in scalar tensor theories [6,7] or to a rank 2 antisymmetric Kalb-Ramond tensor field as in [3,8].…”
Section: Jhep03(2005)039mentioning
confidence: 99%
“…Torsion corresponds to the anti-symmetric part of the Affine connection and shows up when one generalizes Einsteins theory of gravity in such a way that the geometry is not only characterized by the curvature [4]. Torsion can be related to coupling to fermionic fields [5], alternatively it can be associated with a scalar field gradient for bosons in scalar tensor theories [6,7] or to a rank 2 antisymmetric Kalb-Ramond tensor field as in [3], [8].…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that the presence of a gravitational scalar field -which from now on we will call generically as "dilaton" -induces a very similar structure as in the case of a wiggly cosmic string [4]. Further, Bezerra and Ferreira [6] showed that, if a torsion is presented, this effect is amplified.…”
Section: Introductionmentioning
confidence: 99%
“…Various interior solutions have been investigated by Krisch [23]. Spinning strings that may contain torsion have been studied by Anandan [24], and the effect of screwed superconducing cosmic strings in scalar-tensor theories have also been investigated [25]. In this case the torsion was assumed to arise from a scalar field.…”
Section: Introductionmentioning
confidence: 99%